2018
DOI: 10.1111/iwj.13045
|View full text |Cite
|
Sign up to set email alerts
|

Incisional negative pressure therapy reduces complications and costs in pressure ulcer reconstruction

Abstract: Complications after pressure ulcer reconstruction are common. A complication rate of 21% to 58% and a 27% wound recurrence has been reported. The aim of this study was to decrease postoperative wound‐healing complications with incisional negative pressure wound therapy (iNPWT) postoperatively. This was a prospective non‐randomised trial with a historic control. Surgically treated pressure ulcer patients receiving iNPWT were included in the prospective part of the study (Treatment group) and compared with the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…11 Incisional negative pressure wound therapy has been shown to reduce hospitalisation length in pressure ulcer and orthopaedic surgery. 33,34 We found a significant reduction in hospitalisation length in the iNPWT cohort. Reduced hospitalisation is associated with significant benefits to both patient (decreased respiratory and thromboembolic complications) and the community (allocation of resources and access).…”
Section: Discussionmentioning
confidence: 71%
“…11 Incisional negative pressure wound therapy has been shown to reduce hospitalisation length in pressure ulcer and orthopaedic surgery. 33,34 We found a significant reduction in hospitalisation length in the iNPWT cohort. Reduced hospitalisation is associated with significant benefits to both patient (decreased respiratory and thromboembolic complications) and the community (allocation of resources and access).…”
Section: Discussionmentioning
confidence: 71%
“…[68] It has been reported that its prevalence rate varies from 8.8% to 53.2%, and its incidence rate ranges from 7% to 71.6%. [9–12] Additionally, this order has also been associated with an increased incidence of infection, [13,14] and can greatly decrease quality of life in patients with PU. [15,16]…”
Section: Introductionmentioning
confidence: 99%
“…The included studies represent a global surgical patient population with 7451 patients receiving ciNPT and 16,085 patients receiving SOC across 16 countries. 11–16,20–97 The countries represented included the USA (n = 42), Germany (n = 11), Australia (n = 6), Canada (n = 5), Italy (n = 4), Spain (n = 3), the UK (n = 3), Denmark (n = 2), and one each from Austria, Brazil, France, Ireland, the Netherlands, South Africa, Taiwan, and Turkey. Dressings used in the SOC population varied and included gauze dressings, antimicrobial hydrofiber dressings, absorbent dressings, hydrocolloid dressings, occlusive dressings, or foam dressings.…”
Section: Resultsmentioning
confidence: 99%
“…The 84 studies identified encompassed cardiac surgery (n = 8), general abdominal surgery (n = 21), obstetric and gynecologic surgery (n = 8), orthopedic surgery (n = 16), plastic surgery (n = 16), and vascular surgery (n = 15). 11–16,20–97…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation